Melioidosis in 6 tsunami survivors in southern Thailand. - Chierakul, W; Winothai, W; Wattanawaitunechai, C; Wuthiekanun, V; Rugtaengan, T; Rattanalertnavee, J; Jitpratoom, P; Chaowagul, W; Singhasivanon, P; White, N; Day, N; Peacock, S (2005)
BACKGROUND: Six cases of melioidosis were identified in survivors of the 26 December 2004 tsunami who were admitted to Takuapa General Hospital in Phangnga, a region in southern Thailand where melioidosis is not endemic. All 6 cases were associated with aspiration, and 4 were also associated with laceration. METHODS: We compared the clinical, laboratory, and radiographic findings and the outcomes for these 6 patients with those for 22 patients with aspiration-related melioidosis acquired during 1987-2003 in a melioidosis-endemic region in northeast Thailand. Results of tests for detection of Burkholderia pseudomallei in soil specimens from Phangnga and from northeast Thailand were compared. RESULTS: The 6 patients (age range, 25-65 years) presented with signs and symptoms of pneumonia 3-38 days (median duration, 6.5 days) after the tsunami. Chest radiograph findings at the onset of pneumonia were abnormal in all cases; 1 patient developed a lung abscess. B. pseudomallei was grown in blood cultures in 3 cases and in cultures of respiratory secretions in 4 cases. Two patients required ventilation and inotropes; 1 patient died. Compared with tsunami survivors, patients with aspiration-related melioidosis in northeast Thailand had a shorter interval (median duration, 1 day) between aspiration and onset of pneumonia; were more likely to exhibit shock, respiratory failure, renal failure, and/or altered consciousness (P=.03); and had a higher in-hospital mortality (64% [14 of 22 patients]; P=.07). These differences may be related to the severity of the near-drowning episode, the inhalation of sea water versus fresh water, the size of bacterial inoculum, and the possible acquisition (among tsunami survivors) of B. pseudomallei via laceration. Only 3 (0.8%) of 360 soil samples from Phangnga were positive for B. pseudomallei, compared with 26 (20%) of 133 samples from northeast Thailand (P<.0001). CONCLUSIONS: Tsunami survivors are at increased risk of melioidosis if they are injured in an environment containing B. pseudomallei.